Reduced order modeling of a short-residence time gasifier. (1st December 2015) - Hossein Sahraei, M.; Duchesne, Marc A.; Yandon, Robert; Majeski, Adrian; Hughes, Robin W.; Ricardez-Sandoval, Luis A.
Highlights: A reactor network is presented for the modeling of CanmetENERGY's gasifier. Axial velocity, molar composition and temperature profiles are presented. The model is compared to the results of corresponding CFD simulation. Abstract: State-of-the-art gasifiers require rapid mixing of fuel, steam and oxygen to achieve high carbon conversion within a short residence time. This allows reduction of the gasifier's volume and the associated capital costs. CanmetENERGY of Natural Resources Canada has a pilot-scale gasifier that can convert solid fuels to syngas in less than 1 s. This study describes the development of a reduced order model (ROM) for CanmetENERGY's entrained flow short-residence time gasifier. The model consists of a reactor network that represents the gasifier using a set of chemical reactors that are aimed to capture distinct flow zones of the system. The layout of chemical reactors proposed in this work is based on computational fluid dynamics (CFD) simulations of the gasifier that accounted for the detailed gas and particle flows. The ROM implements sub-models for the simulation of drying, devolatilization, chemical reactions, viscous fluid–solid interactions, pollutant formation and heat transfer through the wall of the reactor. The predictions obtained by the ROM are in reasonable agreement with the CFD simulation data for axial temperature, heat flux, conversion and composition. Having established the flow pattern for a given gasifier and range of operating conditions, the proposed ROM is computationally efficient since it only requires 2.5 min to converge whereas CFD simulations require 7–10 days. This attractive feature enables integration of the gasifier ROM to process simulators for further development of integrated gasification combined cycle power plants.